Alizarin Red S-Alcian Blue Staining for Regenerated tail of Common House Gecko (Hemidactylus frenatus) - Rakhmiyati Rakhmiyati; Muhammad Ja’far Luthfi (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2018)
Common House Gecko (Hemidactylus frenatus) is one of reptiles that have ability to autotomy their tails. Tail autotomy is a mechanism to protect it self from predators. After the tail broke, there will be wound healing on the tail which is then followed by a tail regeneration event. Original tail and regenerate tail is very different morphologically and anatomically. The original tail is composed of bones while the tail of the regenerate is composed of cartilage. Histochemical staining using Alizarin Red-S Alcian Blue was done to differentiate bone and cartilage. This method will stained bones red while the cartilage will stained blue.